Innovative learning methods of Islamic education subject in Indonesia: a meta-analysis - Anuraga Jayanegara; Asrori Mukhtarom; Ismail Marzuki (Institute of Advanced Engineering and Science, 2024)
This study aimed to evaluate the effects of innovative learning methods in the Islamic education (ISE) subject on learning motivation, learning activity, and learning achievement of students in the elementary and secondary schools in Indonesia. This study employed the meta-analysis method which is among the quantitative research approach. There were 47 literatures that eligible to be included in the database. Results revealed that, for the learning motivation variable, effect size value in the form of odds ratio was significantly higher than 1.0 (average 3.008 [2.020-4.480]; P<0.001). For the learning activity variable, effect size value was significantly higher than 1.0 (average 2.905 [2.113-3.994]; P<0.001). For the learning achievement variable, effect size value was significantly higher than 1.0 (average 4.941 [4.136-5.903]; P<0.001). These indicated that innovative learning methods were able to elevate learning motivation, activity and achievement. There were no significant differences among the categories within most of the sub-groups, except for the sub-group of cycle, in which cycle 2 showed higher learning achievement than that of cycle 1 (P<0.05). It can be concluded that innovative learning methods are able to elevate learning motivation, learning activity, and learning achievement of students at elementary and secondary schools to study the Islamic education subject. Future work should address the interaction between each particular innovative learning method and the ISE specific topic.